2015
DOI: 10.1149/2.0221505jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance of Carbon/MnO2Nanocomposites Prepared via Molecular Bridging as Supercapacitor Electrode Materials

Abstract: The chemical binding of amorphous manganese oxide and carbon particles was achieved with the diazonium chemistry. The synthesis was performed in two steps, with a first step consisting in the surface functionnalization of carbon particles with aminophenyl groups and the subsequent attachment of amorphous manganese oxide particles through generated phenyl groups. The bond between carbon and MnO 2 particles is believed to occur between the carbon from the phenyl groups attached to carbon particles, and the oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…The chemical bridging between MnO 2 and carbon particles has been achieved by diazonium chemistry. [ 29 ] It has been demonstrated that this approach allowed for improved mixing of MnO 2 and carbon particles and facilitated charge transfer. [ 29 ] The capacitance of the carbon/MnO 2 grafted nanocomposite electrode was doubled compared to a simple mixture of its two components.…”
Section: Manganese Oxides and Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical bridging between MnO 2 and carbon particles has been achieved by diazonium chemistry. [ 29 ] It has been demonstrated that this approach allowed for improved mixing of MnO 2 and carbon particles and facilitated charge transfer. [ 29 ] The capacitance of the carbon/MnO 2 grafted nanocomposite electrode was doubled compared to a simple mixture of its two components.…”
Section: Manganese Oxides and Compositesmentioning
confidence: 99%
“…[ 29 ] It has been demonstrated that this approach allowed for improved mixing of MnO 2 and carbon particles and facilitated charge transfer. [ 29 ] The capacitance of the carbon/MnO 2 grafted nanocomposite electrode was doubled compared to a simple mixture of its two components. [ 29 ] In another investigation, [ 50 ] it was found that sulfasalazine molecules adsorbed on MnO 2 and carbon nanotubes.…”
Section: Manganese Oxides and Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…They grafted electroactive anthraquinone (AQ) groups on high specific surface area carbon, afterwards the specific capacitance was doubled because the grafted AQ groups had redox capacitance. [49][50][51] In the latest research of Brousse and Belanger et al, 52 they prepared carbon/MnO 2 nanocomposites via molecular bridging.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] Alternatively, pseudocapacitors developed from the surface redox process exhibit higher charge densities but suffer from slower charge transfer kinetics compared to EDLCs. 1,7,8 Hence, one of the most critical aspects in the development of supercapacitor technologies is to provide higher energy and power delivery, while maintaining excellent cycle stability.…”
Section: Introductionmentioning
confidence: 99%